Perspectives on global fermented foods. Issue 11 (28th October 2014) - Renko, Sanda; Soni, Surabhi; Dey, Gargi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to outline the present status of various fermented foods and beverages across the globe and reviews on the microbiology and therapeutic effects of fermented foods. Design/methodology/approach – Fermented foods play an important socio-economic role in developing countries as well as making a major contribution to the nutrition requirements of natural populations. These foods have attracted attention all over the world as foods that might promote longevity. The approach is based on observations of online research with respect to fermented foods and their origins, analysis of research papers in journals and systematic research on the microbiology and health benefits of fermented products. Findings – In general, traditional fermented foods produced with indigenous practices throughout the world are made under primitive conditions, which result in low yield and poor quality. But since, these foods are not only traditional but also functional foods. They are experiencing a burst of popularity as health foods worldwide. The raw materials traditionally used for fermentation are as diverse as: fruits, cereals, vegetables, milk, meat, and fish. It is possible to obtain a large variety of different food products by selecting different raw materials, starter cultures, and fermentation conditions. Originality/value – The paper offers a holistic view that would guide a reader to identify various fermented products and enlighten them about their therapeutic properties.